2010
DOI: 10.1001/archinternmed.2010.199
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of the Pulmonary Embolism Severity Index for Prognostication in Patients With Acute Symptomatic Pulmonary Embolism

Abstract: The simplified PESI has similar prognostic accuracy and clinical utility and greater ease of use compared with the original PESI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
778
12
60

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,114 publications
(869 citation statements)
references
References 26 publications
19
778
12
60
Order By: Relevance
“…3 Certain ECG characteristics have been shown to be associated with RHS but typically are not incorporated in the risk-stratification models. 4,16 In this study, we found 3 ECG characteristics independently associated with RHS: TWI in leads V 1 through V 3 , S wave in lead I, and sinus tachycardia. We derived a simple, easyto-use, 10-point ECG score that can effectively risk-stratify 85% of acute PE patients.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…3 Certain ECG characteristics have been shown to be associated with RHS but typically are not incorporated in the risk-stratification models. 4,16 In this study, we found 3 ECG characteristics independently associated with RHS: TWI in leads V 1 through V 3 , S wave in lead I, and sinus tachycardia. We derived a simple, easyto-use, 10-point ECG score that can effectively risk-stratify 85% of acute PE patients.…”
Section: Discussionsupporting
confidence: 49%
“…15 This timeframe was chosen based on prior literature and is consistent with a typical length of hospitalization for PE. 16 …”
Section: Secondary Outcome and Subanalysismentioning
confidence: 99%
“…Similar to the above parameters, PESI score was initially devised to predict mortality and to identify low-risk patients who may be candidates for outpatient treatment or abbreviated hospital stay [16]. sPESI, with similar prognostic accuracy, reduces complexity by including 6 of the 11 original PESI variables [7], and we aimed to analyze the usefulness of PESI and sPESI scores to predict LOS in normotensive patients with acute PE. Our investigation showed that a PESI score of <85 points and a sPESI score of 0 (low-risk class) identified patients at low risk and accurately predicted short LOS.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we included patients with acute symptomatic PE from March 2001 to July 2017. We compared the demographics, comorbidities (such as underlying coronary disease, heart failure, and atrial fibrillation) as well as the baseline simplified PE severity index (sPESI)8 and PESI9 in PE patients with versus those without early TTE. We used a generalized linear mixed model, with random effect for enrolling centers, to determine significant predictors of early TTE.…”
Section: Methodsmentioning
confidence: 99%